Method for preparing laser-induced graphene-based conformal supercapacitor from MXene precursor assisted by graphene oxide
Through the combination of graphene oxide-assisted MXene precursor and laser induction technology, the problem of limited capacity of laser-induced graphene electrodes is solved, capacity improvement and effective removal of active substances are achieved, and the potential for conformation application is achieved.
Patent Information
- Application Number
- CN202411774189.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
The simple laser-induced graphene electrode has limited capacity in supercapacitors, and there are process compatibility problems and difficulty in introducing and removing active substances.
The laser-induced graphene-based conformal supercapacitor was prepared by using graphene oxide-assisted MXene precursor. Through self-assembly composite materials and laser induction technology, capacity improvement and effective removal of excess active substances were achieved.
The capacity of the supercapacitor is significantly improved and the possibility of conformal application is provided, ensuring that the full introduction of active substances and the removal of excesses do not affect subsequent device integration.
Smart Images

Figure CN119581239A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitor preparation, and specifically relates to a method for preparing a laser-induced graphene-based conformal supercapacitor using a graphene oxide-assisted MXene precursor. Background Art
[0002] Laser-induced graphene (LIG) technology is inexpensive, flexible, fast, and does not require masks or complex subsequent processing. It is an efficient and rapidly integrated processing method. Using laser-induced graphene (LIG) as an electrode has huge advantages in the preparation of supercapacitors, but pure laser-induced graphene electrodes have the problem of limited capacity. In order to increase the capacity of LIG-based supercapacitors, LIG electrodes can be modified by electrochemical activation, heteroatom doping, and introduction of active materials. However, the full introduction of active substances and the effective removal of excess active substances still face challenges. First, there are process compatibility issues between the introduction of active substances and the laser-induced graphene process. Second, incomplete removal of excess active substances affects subsequent device integration. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a laser-induced graphene-based conformal supercapacitor using a graphene oxide-assisted MXene precursor. The method proposes an active material that is compatible with the laser-induced process and easy to remove, and utilizes the weak adhesion of graphene oxide to a polyimide (PI) substrate, through the principle of synergistic material self-assembly and the principle of laser-matter interaction, to prepare a supercapacitor with significantly improved capacity and conformal application prospects.
[0004] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a laser-induced graphene-based conformal supercapacitor using a graphene oxide-assisted MXene precursor comprises the following steps:
[0005] (1) Preparation of self-assembled graphene oxide-MXene composite precursor
[0006] A 5 mg / mL graphene oxide (GO) aqueous solution and a 2 mg / mL MXene aqueous solution were mixed in a mass ratio of 10:1 between graphene oxide and MXene, and then stirred continuously under inert gas protection to form a uniform and stable solution for later use;
[0007] (2) Preparation of LIG-based electrodes based on self-assembled graphene oxide-MXene composite precursors
[0008] ① The PI film was cleaned with ethanol and deionized water and dried, and then 2 mL of the prepared self-assembled graphene oxide-MXene solution was evenly coated on the PI film and dried under an inert gas protection environment. The sample was recorded as PI-C;
[0009] ② The parameters of the ultraviolet laser were set to a laser wavelength of 405nm, a laser power of 3.0W, and a laser scanning speed of 50mm / s. According to the designed interdigital pattern, the laser acted on the sample PI-C, and the laser action area turned black visibly to the naked eye, and a LIG-based supercapacitor interdigital electrode based on graphene oxide-MXene was obtained; in the area where the laser was not applied, the excess graphene oxide-MXene composite material was gently removed with an ear cleaning bulb;
[0010] ③Silver wires are adhered to both sides of the interdigital electrodes of the LIG-based supercapacitor, and phosphoric acid-polyvinyl alcohol (H3PO4-PVA) gel electrolyte is coated on the interdigital electrode area. The entire device is then placed in a fume hood to dry naturally. The device is assembled and a LIG-based supercapacitor is obtained.
[0011] Conformal demonstration of LIG-based supercapacitors
[0012] In order to meet the requirements of anti-deformation ability in actual wearable applications, supercapacitors need to have the characteristics of conformal with electronic devices. Therefore, it is necessary to conduct conformal testing and characterization on the assembled LIG-based supercapacitors. The specific operation is to perform cyclic voltammetry (CV) tests on the assembled devices under different bending states at a scanning speed of 100mV / s to observe the stability of its electrochemical performance under different conformal conditions.
[0013] Integrated demonstration of LIG-based supercapacitors
[0014] In order to meet the needs of practical applications, on the basis of a single LIG-based supercapacitor, it is also necessary to prepare it in an integrated manner, such as processing tandem devices to achieve voltage expansion and power actual electronic devices. Specific steps:
[0015] ① Laser-inducing PI-C according to the pre-designed tandem device pattern to remove excess active material and obtain tandem device electrodes;
[0016] ② Assembling the prepared series device electrodes, including gluing silver wires, coating phosphoric acid-polyvinyl alcohol (H3PO4-PVA) gel electrolyte, and then placing the entire device in a fume hood to dry naturally, and the device assembly is completed;
[0017] ③ At the same scan rate (100mV / s) and current density (0.10mA / cm 2 ) were used to conduct CV and constant current charge and discharge (GCD) tests to study the specific performance of the integrated device.
[0018] Through the above-mentioned design scheme, the present invention can bring the following beneficial effects: Since the present invention combines the advantages of material self-assembly technology and laser induction technology, the stacking of MXene with pseudocapacitive characteristics is improved under the regulation of graphene oxide, and it is successfully introduced into LIG. At the same time, due to the poor adhesion of graphene oxide to the PI substrate, the excess MXene is also easily removed. Therefore, the capacity of the LIG-based supercapacitor based on the graphene oxide-MXene composite material is significantly improved. At the same time, due to the selection of the PI substrate, the LIG-based supercapacitor based on the graphene oxide-MXene composite material shows the possibility of conformal application. Graphene oxide is not used as an active substance here, but as an auxiliary material. On the one hand, it regulates the properties of the MXene active substance, and on the other hand, it ensures the effective removal of excess active materials. Integrated devices can also be realized and show good possibilities for practical applications. The precursor scheme of the present invention combines material properties and makes full use of physical principles, and maximizes the modification of the performance of the supercapacitor with a simple ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings herein are used to provide a further understanding of the present invention and constitute a part of the present application. The exemplary embodiments of the present invention and their descriptions are used to understand the present invention and do not constitute improper limitations of the present invention. In the accompanying drawings:
[0020] Figure 1 Schematic diagram of the preparation of a laser-induced graphene-based conformal supercapacitor reinforced with a self-assembled graphene oxide-MXene composite material according to the present invention
[0021] Figure 2 The performance difference of the supercapacitor prepared by the self-assembled graphene oxide-MXene composite precursor of the present invention relative to the original laser induced graphene (LIG), pure graphene oxide precursor (LIG-RGO), and pure MXene precursor (LIG-M).
[0022] Figure 3 The CV curves under different states are shown for the conformal application of the laser-induced graphene supercapacitor based on the self-assembled graphene oxide-MXene composite precursor of the present invention;
[0023] Figure 4 The capacitance retention rate of the laser-induced graphene supercapacitor under different bending states compared with the initial state in the conformal application demonstration of the present invention based on the self-assembled graphene oxide-MXene composite precursor;
[0024] Figure 5 The figure is a bending cycle test result diagram of the conformal application of the laser-induced graphene supercapacitor based on the self-assembled graphene oxide-MXene composite precursor of the present invention;
[0025] Figure 6 This is a schematic diagram showing the integrated device application of the laser-induced graphene supercapacitor based on the self-assembled graphene oxide-MXene composite precursor of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical scheme of the present invention is clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the present invention is not limited to the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. In order to avoid confusing the essence of the present invention, the known methods, processes, procedures, components and circuits are not described in detail.
[0027] Please also read Figure 1 , Figure 2 , Figure 3 and Figure 4 The present invention proposes a method for preparing a self-assembled graphene oxide-MXene composite material using graphene oxide as an auxiliary material as an easily removable precursor to enhance the performance of laser-induced graphene electrodes for conformal supercapacitors.
[0028] The present invention is based on the principle of laser-matter interaction and the principle of material self-assembly, and adopts a simple laser-induced process to provide a self-assembled composite material with significantly improved performance and conformal application of LIG-based supercapacitors and a preparation method thereof. The development of a composite precursor that can ensure the full introduction of active substances and remove excess active substances without affecting the subsequent integration of the device and is compatible with the laser-induced process is achieved. The self-assembled composite precursor material makes full use of the electronegativity of the graphene oxide-MXene material. The combination of the two can fully break the long-range structure of the graphene oxide-MXene sheet layer, and effectively prevent the stacking of MXene particles from affecting the modification effect on LIG. At the same time, due to the poor adhesion of graphene oxide to the PI substrate, the excess MXene particles can be easily removed without affecting the further integrated preparation of subsequent LIG-based devices. Here, graphene oxide is used as an auxiliary material rather than an active substance, and its main function is to modify the active material to be introduced and provide the possibility for the subsequent removal of residual active material materials. Compared with the method without the participation of graphene oxide, the direct use of MXene particles is simpler to operate and the device performance modification is more obvious.
[0029] Example 1
[0030] ① First, prepare the self-assembled graphene oxide-MXene composite material
[0031] The graphene oxide aqueous solution and the MXene aqueous solution are mixed in a ratio of 10:1 of graphene oxide to MXene by mass, and stirred continuously under an inert gas until a uniform and stable liquid is formed, thereby obtaining a graphene oxide-MXene composite material;
[0032] ② Take 2 mL of graphene oxide-MXene composite material and apply it on a clean PI film (i.e. Figure 1 PI substrate), dried naturally under the protection of inert gas, recorded as PI-C, and used for later use;
[0033] ③Use ultraviolet laser with a wavelength of 405nm, a power of 3.0W, and a scanning speed of 50mm / s to act on PI-C according to the designed interdigital pattern. Where the laser acts, PI-C is transformed into LIG-C;
[0034] ④ Gently blow air with an ear-cleaning bulb to remove the graphene oxide-MXene composite material in the unaffected area to obtain the LIG-C interdigital electrode;
[0035] ⑤ Attach silver wires on both sides of the LIG-C interdigital electrodes, coat the interdigital electrode area with H3PO4-PVA gel electrolyte, and then place the entire device in a fume hood to dry naturally. After the device is assembled, perform electrochemical testing.
[0036] Example 2
[0037] ① Under the same experimental conditions, original PI film, PI film coated with graphene oxide, and PI film directly coated with MXene were used, and dried naturally under the protection of inert gas, and recorded as PI, PI-GO, and PI-M for standby use;
[0038] ②Using ultraviolet laser with a wavelength of 405nm, a power of 3.0W and a scanning speed of 50mm / s, PI, PI-GO and PI-M were acted on according to the designed interdigital pattern. The areas where the laser acted were converted into LIG, LIG-RGO and LIG-M respectively.
[0039] ③ Removing the graphene oxide-MXene composite material in the unaffected area to obtain LIG interdigitated electrodes, LIG-RGO interdigitated electrodes, and LIG-M interdigitated electrodes;
[0040] ④ As with the LIG-C interdigital electrode, silver wires were adhered to both sides of the LIG interdigital electrode, LIG-RGO interdigital electrode, and LIG-M interdigital electrode, and H3PO4-PVA gel electrolyte was coated on the interdigital electrode area. The entire device was then placed in a fume hood to dry naturally. After the device was assembled, LIG supercapacitors, LIG-RGO supercapacitors, LIG-M supercapacitors, and LIG-C supercapacitors were obtained for electrochemical testing;
[0041] ⑤Set the scan speed to 10mV / s and collect CV curves of different samples, such as Figure 2 As shown, according to the calculation formula: Where I is the current, v is the scanning speed, A is the electrode area, S is the scanning speed, V H is the discharge start voltage, V L is the discharge end voltage, ΔV=V H -V L , ΔV is the voltage window, and the capacities of LIG supercapacitor, LIG-RGO supercapacitor, LIG-M supercapacitor and LIG-C supercapacitor are 0.57 mF / cm 2 , 0.62mF / cm 2 , 0.86mF / cm 2 , and 2.33mF / cm 2 , which fully demonstrates the superiority of the graphite oxide-MXene ratio scheme.
[0042] Example 3
[0043] ① The prepared LIG-C supercapacitor was subjected to electrochemical tests at four different bending angles and compared with the electrochemical performance in the initial state; the initial state was the device in a flat state, bending state 1 corresponded to a curvature radius of 18 mm, bending state 2 corresponded to a curvature radius of 15 mm, bending state 3 corresponded to a curvature radius of 12 mm, and bending state 4 corresponded to a curvature radius of 10 mm.
[0044] ② Set the scan speed to 100mV / s, and collect CV curves under different conditions, such as Figure 3 As shown;
[0045] ③ Calculate the percentage ratio of the retention rate shown by the CV curve under different bending states to the retention rate under the initial state, such as Figure 4 As shown, the retention rates of bending state 1, bending state 2, bending state 3, and bending state 4 are 99.8%, 99.8%, 99.3%, and 99.1%, respectively, with excellent conformal potential;
[0046] ④ Perform 1000 bending cycles at a bending angle close to that of a wearable device. Figure 5 As shown, the percentage ratio of the retention rate shown by the CV curve to the retention rate in the initial state is as high as 103%, which fully demonstrates the stability of the device.
[0047] Example 4
[0048] Design three LIG-C electrode patterns in series, and then process them with a UV laser at a laser power of 3.0 W and a laser scanning speed of 50 mm / s;
[0049] Silver wires were attached to both sides of three LIG-C interdigital electrodes connected in series, and H3PO4-PVA gel electrolyte was coated on the interdigital electrode area. The entire device was then placed in a fume hood to dry naturally, and the integrated device was assembled.
[0050] At a scan rate of 100 mV / s, CV curves of single devices and integrated devices were collected, and the voltage was extended from 0.8 V to 2.4 V. See Figure 6 (a);
[0051] At 0.1 mA / cm 2 The GCD curves of single devices and integrated devices were tested at a current density of , and the voltage was also extended from 0.8V to 2.4V. Figure 6 (b);
[0052] Due to the expansion of the voltage window, the integrated device can power the LED, that is, it can light up an LED under discharge conditions.
Claims
1. A method for preparing laser-induced graphene-based conformal supercapacitors using graphene oxide-assisted MXene precursors, characterized in that: The method comprises the following steps: Step 1: Preparation of self-assembled graphene oxide-MXene composite precursor The graphene oxide aqueous solution and the MXene aqueous solution are mixed, and continuously stirred under the protection of an inert gas to form a uniform and stable solution to obtain a self-assembled graphene oxide-MXene solution for later use; Step 2: Preparation of LIG-based electrodes based on self-assembled graphene oxide-MXene composite precursors ① The PI film was cleaned with ethanol and deionized water and dried, and then the prepared self-assembled graphene oxide-MXene solution was evenly coated on the PI film and dried under an inert gas protection environment. The sample was recorded as PI-C; ②According to the designed interdigital pattern, the sample PI-C was acted on by laser, and the laser-acted area turned black visibly, thus obtaining the LIG-based supercapacitor interdigital electrode based on graphene oxide-MXene composite material; in the area not acted on by laser, the excess graphene oxide-MXene composite material was gently removed with an ear-cleaning bulb; ③ Attach silver wires on both sides of the interdigital electrodes of the LIG-based supercapacitor, coat the interdigital electrode area with phosphoric acid-polyvinyl alcohol gel electrolyte, and then place the entire device in a fume hood to dry naturally. The device is assembled.
2. The method for preparing a laser-induced graphene-based conformal supercapacitor using graphene oxide-assisted MXene precursor according to claim 1, characterized in that: In step 1, a graphene oxide aqueous solution with a concentration of 5 mg / mL and a MXene aqueous solution with a concentration of 2 mg / mL are mixed in a mass ratio of graphene oxide to MXene of 10:
1.
3. The method for preparing a laser-induced graphene-based conformal supercapacitor using graphene oxide-assisted MXene precursor according to claim 1, characterized in that: The laser wavelength was set to 405 nm, the laser power to 3.0 W, and the laser scanning speed to 50 mm / s.
4. The method for preparing a laser-induced graphene-based conformal supercapacitor using graphene oxide-assisted MXene precursor according to claim 1, characterized in that: Take 2 mL of the prepared self-assembled graphene oxide-MXene solution and evenly coat it on the PI film.